Novel yeast taxa from the cold: description of Cryolevonia giraudoae sp. nov. and Camptobasidium gelus sp. nov. - de Garcia, Virginia (2020)
Twenty-one psychrophilic yeast isolates related to the Camptobasidiaceae family in the Microbotryomycetes class were obtained from ice collected from cold environments worldwide. A new psychrophilic species from the recently described genus Cryole-vonia, Cryolevania giraudoae is proposed to accommodate 18 isolates from Patagonia (Argentina) and Antarctica (holotype CRUB 2086T). In addition, a new psychrophilic species in the genus Camptobasidium is described as Camptobasidium gelus sp. nov. (holotype CBS 8941T), based on three isolates from glacial ice in the Russel glacier (Greenland ice sheet) and Antarctica. The strict psychrophilic profile is the salient feature of both novel species.